Thickness Dependent Nanostructural, Morphological, Optical And Impedometric Analyses Of Zinc Oxide-gold Hybrids: Nanoparticle To Thin Film - Veeradasan Perumal; Uda Hashim; Subash C.B. Gopinath; R. Haarindraprasad; Wei-Wen Liu; P. Poopalan; S. R. Balakrishnan; V. Thivina; A. R. Ruslinda (Public Library of Science, 2024)
Non-Indexed Publication